IPTEKS PENGHITUNGAN PAJAK PERTAMBAHAN NILAI (PPN) BERBASIS E-FAKTUR (STUDI KASUS PADA PT. BERKAT REHOBOT) - Lumikis, Riri I. C.; Ilat, Ventje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
The applied of knowledge, technology, and art about determining the Value Added Tax (VAT) is very important for a company so not over the government regulations. The company need to know how to determine Value Added Tax (VAT) in case of calculating, recording, and reporting especially while using a system called e-Faktur. PT. Berkat Rehobot is the object for this study in term to give a good example for most of other companies about how to determine Value Added Tax (VAT) in Indonesia according to government regulation number 42 in year 2009 especially with Director General of Tax Regulation No. PER-16 / PJ / 2014.